Seed production of pearlspot (Etroplus suratensis) The State Fish of Kerala - P A, Vikas; Subramannian, Shinoj (Indian Farming, 2024)
Pearlspot (Etroplus suratensis), known as Karimeen, holds cultural and culinary significance in Kerala and is designated the 'State Fish of Kerala'. With an annual demand of 10,000 MT for 'Kerala Karimeen' far exceeding the production of 2,000 MT, there is a growing interest in pearlspot culture. However, limited availability of seeds, with an annual requirement of 40 million, poses a critical challenge. Addressing the low fecundity and unique reproductive behaviours of pearlspot, this article introduces an innovative seed production approach in pond systems. The article emphasizes pond preparation for optimal conditions, brood fish management, facilitatingbreeding environments, breeding behaviours etc. are explored. Parental care, predator control, economic and marketing aspects are also discussed. The innovative pond system approach emerges as a promising solution for making quality seeds available for pearlspot aquaculture.